Absence of Epstein-Barr virus RNA in multiple sclerosis as assessed by in situ hybridisation. Issue 8 (August 1994) - Hilton, D A; Love, S; Fletcher, A; Pringle, J H
Abstract : Epidemiological and serological evidence has suggested a role for Epstein-Barr virus infection in the aetiology of multiple sclerosis. Epstein-Barr virus-specific RNA was looked for in the brains of 10 patients with multiple sclerosis by in situ hybridisation. A total of 21 plaques was examined. In all of these preservation of RNA was shown by hybridisation of control probes to mitochondrial rRNA but no signal was detected with the Epstein-Barr virus probes. It is unlikely that persistent or latent Epstein-Barr virus infection of the CNS occurs in multiple sclerosis, although present findings do not exclude a role for Epstein-Barr virus in the initiation of this disorder.